2021
DOI: 10.1021/acssuschemeng.1c05850
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering of CoS2–CeO2/Ti Nanocatalyst for Artificial N2 Fixation

Abstract: The development of a highly selective electrocatalytic nitrogen reduction ammonia catalyst is an attractive and challenging task. In this letter, we reported the construction of a CoS2–CeO2 load on Ti mesh (CoS2–CeO2/Ti) based on interface engineering, which can be used as a highly efficient electrocatalytic nitrogen reduction reaction (NRR) catalyst under environmental conditions. According to density functional theory (DFT) calculations, N2 can be activated by the low-coordinated Co atom of the CoS2(110) sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…S23†). As shown, increasing the N-doping level did not enhance the NH 3 yields, and the optimal NRR performance was still 12.2 μg h −1 cm cat −2 for the CoS x /CC-L sample at −0.2 V. As a consequence, the HER and NRR results for different N-doped samples indicated that N doping may affect the electrocatalytic performance, but HER and NRR activities were mainly derived from amorphous CoS x in CoS x /CC-L. For comparison, the performance of the CoS x /CC-L was better than or comparable to most of the previously reported NRR catalysts 43–54 under neutral conditions, as illustrated in Table S3 †. In addition, the synthesis of sulfide by a laser combined with a H 2 S atmosphere is a universal method.…”
Section: Resultsmentioning
confidence: 92%
“…S23†). As shown, increasing the N-doping level did not enhance the NH 3 yields, and the optimal NRR performance was still 12.2 μg h −1 cm cat −2 for the CoS x /CC-L sample at −0.2 V. As a consequence, the HER and NRR results for different N-doped samples indicated that N doping may affect the electrocatalytic performance, but HER and NRR activities were mainly derived from amorphous CoS x in CoS x /CC-L. For comparison, the performance of the CoS x /CC-L was better than or comparable to most of the previously reported NRR catalysts 43–54 under neutral conditions, as illustrated in Table S3 †. In addition, the synthesis of sulfide by a laser combined with a H 2 S atmosphere is a universal method.…”
Section: Resultsmentioning
confidence: 92%
“…In another study, Ti mesh supported CoS 2 –CeO 2 based on interface engineering was developed by Zhou et al for the NRR, and an NH 3 yield of 3.33 × 10 −10 mol s −1 cm −2 with a FE of 2.52% was achieved at −0.5 V in 0.1 M Na 2 SO 4 . 86 It is suggested that the low-coordination Co in CoS 2 could effectively activate N 2 and the oxygen-containing CeO 2 could adsorb H 2 O to provide H + for the NRR, thereby reducing the overpotential of the NRR.…”
Section: Metal Sulfides For the Nrrmentioning
confidence: 99%
“…Due to unique properties including multivalence, easily formed oxygen vacancies and high chemical stability, ceria (CeO 2 ) based catalysts have shown promising electrocatalytic performance for the NRR, such as CoS 2 –CeO 2 /Ti, Bi 4 V 2 O 11 /CeO x , Ru/CeO 2 -Vo and r-CeO 2 nanorods. 15–18 The current works have revealed that oxygen vacancy and Ce 3+ in CeO 2 are beneficial for its catalytic activity, which could serve as a surface active site for gas adsorption, electron capture and reactant activation. 19,20 However, pure CeO 2 with low oxygen defect concentration still exhibits low electrocatalytic performance for the NRR.…”
Section: Introductionmentioning
confidence: 99%